Aile Hekimlerinin İş Doyumu: Adana İl Merkezinden Bir Çalışma - İbrahim Efe EFEOĞLU (Cukurova Medical Journal, 2013)
Purpose: The aim of this study is to determine job satisfaction of family physicians who work in the centre of Adana province. Material and Methods: 458 family physicians working in Adana are listed and 152 physicians were included in the study by making randomization by a third. 17 questionnaires were not included in the study due to the lack of data. The data were evaluated from 135 questionnaires. The survey includes socio-demographic characteristics (age, gender, marital status) and eight items questioning job satisfaction. "Five-point Likert Scale" was used to score the survey questions, and the data, transferred to a computer, were statistically analyzed. Results: Job satisfaction of 135 family physicians, participating in our study, was found slightly above the average. No statistically significant correlation was found between job satisfaction and age, sex, and marital status. 42.2% of the participants reported that their jobs secure their future; 32.6% of the participants reported that their jobs provide adequate salary and promotion chances; 25.2% reported that their jobs provide personal development; 36,3% reported that they feel appreciated when they are performing their jobs; 61,4% reported that they take pleasure in their jobs; 62.2% reported that they are not thinking of changing their jobs; 77,8% reported that most of the time they are willing to perform their work. Conclusion: It has been thought that the outcomes of this study would contribute to develop local solutions and become a reference for future studies in the following years.